Pendampingan Menyusun Laporan Keuangan pada UMKM Aurora Gift Palangka Raya - Septa Soraida; Irma Yani; Natasya Erisya; Umie Watie; Sepiyanti Sepiyanti; Delva Delva (JPMNT JURNAL PENGABDIAN MASYARAKAT NIAN TANA, 2025)
Micro, Small and Medium Enterprises so far can’t be underestimated because even though their businesses are relatively small, they have a tremendous impact on the country. MSMEs have an important role in the Indonesian economy as shown by their contribution of more than 60% to the national Gross Domestic Product (GDP) and absorbing almost 97% of the workforce, and to date the number of MSMEs has reached more than 64 million business units. Although MSMEs have the largest contribution to GDP, it does not automatically increase taxes. One of the problems that occurs is the contribution of tax revenue and the number of taxpayers from MSMEs is still very small. One of the common problems for MSMEs is the inability to prepare financial reports where some have made cash-based records (money in and money out), others have not made any records at all. In addition, another factor that causes MSMEs not to prepare financial reports is the lack of knowledge related to accounting so that they cannot make financial reports. The purpose of this service is to help MSME Aurora Gift to prepare financial reports so that they can be used for decision making.